Who are you? Teaching symbolic interaction and perceptions of the self in the classroom. Issue 2 (3rd April 2019) - Waldbuesser, Caroline
Abstract : Courses: Interpersonal Communication, Fundamentals of Human Communication, Communication Theory, Public Speaking, and Intercultural Communication Objectives: After completing this single-class activity, students will be able to (1) describe how meaning is created through symbolic interaction, (2) explain how the self is created through symbolic interaction, and (3) give examples of their own self-concept that was co-created, reflected upon, and revised through interaction with others in the classroom.